Combined Vitamin D and Magnesium Supplementation Improves Insulin, HOMA Indices, Blood Glucose, and Oxidative Stress Markers in Diabetic Rats - Azzahra, Balqis Faizah; Yueniwati, Yuyun; Permatasari, Happy Kurnia; Rahayu, Rachmi Fauziah; Tifani, Amara Syifa; Fauzi, Adam (The Prodia Education and Research Institute (PERI), 2026)
BACKGROUND: Diabetes mellitus (DM) is characterized by disturbances in glucose homeostasis, chronic low-grade inflammation, and heightened oxidative stress. Alterations in vitamin D status and magnesium homeostasis are frequently observed in DM and have been implicated in impaired insulin secretion, decreased insulin sensitivity, and dysregulated antioxidant responses. Although both micronutrients have independently demonstrated potential benefits on glycaemic regulation and oxidative balance, the synergistic therapeutic effects of combined vitamin D and magnesium supplementation remain insufficiently elucidated in experimental models of type 2 DM. Therefore, this study was conducted to determine the effects of combined vitamin D and magnesium supplementation on insulin dynamics, glycaemic control, and oxidative stress markers in streptozotocin-induced diabetic rats.METHODS: Twenty-four male Wistar white rats were divided into 4 groups: normal control, diabetic control, metformin group, and vitamin D + magnesium group. DM was induced using streptozotocin–nicotinamide injection. Glycaemic parameters including insulin, homeostasis model assessment for insulin resistance (HOMA-IR), and homeostatis model assessment of β-cell function (HOMA-β), were evaluated from fasting serum using immunoassay-based analyses; while oxidative stress markers including superoxide dismutase (SOD) and malondialdehyde (MDA) were measured from plasma using colorimetric spectrophotometric methods.RESULTS: Vitamin D and magnesium combination achieved the greatest reduction in blood glucose. The mean insulin level and HOMA-β index in the vitamin D + magnesium group were significantly higher than in both the diabetic control and metformin groups (p<0.001). In the same group, HOMA-IR and MDA levels were significantly lower, whereas SOD activity was significantly higher compared with diabetic group and metformin group (p<0.001).CONCLUSION: The combination of vitamin D and magnesium increases insulin and HOMA-β level and decreases HOMA-IR, SOD, and MDA expressions in diabetic Wistar rats.KEYWORDS: diabetes mellitus, magnesium, vitamin D, insulin resistance, inflammation